1994
DOI: 10.1002/jcp.1041590320
|View full text |Cite
|
Sign up to set email alerts
|

Tenascin induction in tenascin nonproducing carcinoma cell lines in vivo and by TGF‐β1 in vitro

Abstract: Tenascin, a novel six-armed extracellular-matrix glycoprotein, is expressed in a temporally and spatially restricted pattern during carcinogenesis in association with stromal-epithelial interactions. In this study, we have tested the hypothesis that tenascin expression depends upon the change of the cellular environment from in vitro to in vivo. The distribution and alterations in the expression of tenascin were compared between in vitro and in vivo studies in a variety of human epithelial- and nonepithelial-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
34
1

Year Published

1995
1995
2007
2007

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 51 publications
4
34
1
Order By: Relevance
“…Some collagens, tenascin-C and fibronectin also have common receptors, such as integrins a2b1 and avb3 (Ramos et al 1997). Furthermore, TGF-b not only stimulates collagen synthesis (Fine et al 1990), but also regulates the content of procollagen, fibronectin and tenascin-C (Ignotz et al 1987, McAnulty et al 1991, Sakai et al 1994. These extracellular matrix proteins are obviously closely associated within the process of fibrogenesis.…”
Section: Discussionmentioning
confidence: 96%
“…Some collagens, tenascin-C and fibronectin also have common receptors, such as integrins a2b1 and avb3 (Ramos et al 1997). Furthermore, TGF-b not only stimulates collagen synthesis (Fine et al 1990), but also regulates the content of procollagen, fibronectin and tenascin-C (Ignotz et al 1987, McAnulty et al 1991, Sakai et al 1994. These extracellular matrix proteins are obviously closely associated within the process of fibrogenesis.…”
Section: Discussionmentioning
confidence: 96%
“…Recent studies demonstrated that cancer cells also produce TN in culture or in growing tumor when injected in vivo [23][24][25]. Immunohistochemistry of cancer tissues, including comedo carcinoma of the breast [7] and squamous cell carcinoma and adenocarcinoma of the lung [26], have demonstrated cytoplasmic TN staining, suggesting that cancer cells also produce TN.…”
Section: Discussionmentioning
confidence: 99%
“…A number of these genes are related to the immune response and extracellular matrix and presumably represent targets of glucocorticoid anti-inflammatory action. Many of these proteins are known to be TGF-␤ responsive (e.g., PAI-1, collagens, lysyl oxidase, tenascin, cystatin), but others represent new candidate targets (2,19,23,28). As cellular localization of expression has not been determined, it is possible that some of these genes are primarily expressed and regulated in fibroblasts that contaminate the epithelial cell preparation.…”
Section: Discussionmentioning
confidence: 99%